Impacts of symmetrical and asymmetrical voltage sags on DFIG-based wind turbines considering phase-angle jump, voltage recovery, and sag parameters - Mohseni, Mansour; Islam, Syed; Masoum, Mohammad Sherkat (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2011)
This paper presents a new analysis into the impacts of various symmetrical and asymmetrical voltage sags on doubly fed induction generator (DFIG)-based wind turbines. Fault ride-through requirements are usually defined by the grid codes at the point of common coupling (PCC) of wind farms to the power network. However, depending on the network characteristics and constraints, the voltage sag conditions experienced at the wind generator terminals can be significantly different from the conditions at the PCC. Therefore, it is very important to identify the voltage sags that can practically affect the operation of wind generators. Extensive simulation studies are carried out in MATLAB/Simulink to investigate the transient overshoots and ripples that appear in the rotor current and dc-link voltage when the DFIG is subjected to various types of (a)symmetrical faults. For the first time, the impacts of phase-angle jump and operational constraints of circuit breakers are examined. Furthermore, the influences of sag parameters including type, initial point-on-wave instant, depth, and impedance angle are investigated. Complementary theoretical analyses are also presented to support the validity of observations made in the simulation studies.